2017
DOI: 10.1002/lary.26868
|View full text |Cite
|
Sign up to set email alerts
|

Referral patterns from emergency department to otolaryngology clinic

Abstract: 4. Laryngoscope, 128:1062-1067, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Other studies have reported that the cause of the highest number of referrals from the ED to the otolaryngology clinic was peripheral vertigo, and that the most frequent referral diagnosis was nonspecific vertigo [20]. In such cases, otolaryngologists make a specific diagnosis upon examination.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that the cause of the highest number of referrals from the ED to the otolaryngology clinic was peripheral vertigo, and that the most frequent referral diagnosis was nonspecific vertigo [20]. In such cases, otolaryngologists make a specific diagnosis upon examination.…”
Section: Discussionmentioning
confidence: 99%
“…
Epistaxis is the most common emergency in otolaryngology, 1,2 accounting for up to one third of all emergencies. 3,4 The treatment is discomforting and has a huge socio-economic impact. 5,6 Up to one third of all epistaxis patients in inpatient treatment are taking oral anticoagulants (OAC).
…”
mentioning
confidence: 99%
“…In addition, a high number of them actually do not need to be evaluated in an emergency care unit by an ENT specialist but may necessitate an ENT outpatient clinic visit. [5] The number of patients in our study is a good example of this. We found that over 10,000 patients were seen in a 1-year period in our ENT clinic.…”
Section: Discussionmentioning
confidence: 86%
“…In a study, it was found that the most common diagnoses made were vertigo, external otitis, and nasal fractures, and they concluded that their study was similar to other published hospital audits and epidemiologic studies. [5,6] In another study including 1,067 patients, the most common diseases during the study period were the URTI, acute rhinosinusitis, and tonsillitis. [3] In a study aiming to identify the utilization of EDs by patients with primary otological complaints, the authors found that the most common diagnoses made were otitis media, external otitis, and otalgia.…”
Section: Discussionmentioning
confidence: 99%